Composite material and metal connecting method based on metal surface femtosecond laser etching
Through femtosecond laser etching, the bonding strength between composite materials and metal sheets is improved, and the problems of fiber breakage and bonding fatigue in traditional connection methods are solved, achieving high-strength, wear-resistant metal/composite Material combination.
Patent Information
- Application Number
- CN202411439876.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
AI Technical Summary
The connection method between traditional composite materials and metals has problems such as fiber breakage, stress concentration and poor durability of bonding fatigue in bolt holes, resulting in insufficient structural bearing capacity at the connection parts.
The burr structure is formed based on metal surface femtosecond laser etching technology, and combined with plasma treatment, the chemical energy and activity of metal surfaces are improved, the interlayer bonding strength between composite materials and metal sheets is enhanced, and high-strength metal/composite is obtained through hot pressing molding. Material combination.
A similar mechanical connection effect is achieved, the interface strength and load tolerance between metal and composite materials are improved, the damage to composite materials is reduced, and the characteristics of high specific strength, specific stiffness, low specific gravity, impact resistance, wear and corrosion resistance are obtained. .
Smart Images

Figure CN119319683A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite material and metal connection method based on metal surface femtosecond laser etching, belonging to the technical field of composite material and metal plate interface and bonding. Background Art
[0002] Fiber-reinforced resin-based composite materials have the advantages of high specific strength, specific stiffness and low specific gravity, and have been widely used in the fields of aviation, aerospace, shipbuilding, automobiles, etc. In the design of composite components, it is inevitable to connect with metal, which brings a lot of connection technology problems to the use and installation of composite components. The connecting parts are often the weak link of the overall structure. More than half of the failure positions of composite structural parts occur in the connection parts. Traditional composite-metal connection methods include bolt connection, adhesive connection, bolt + adhesive mixed connection, etc. Usually, when the layers are connected by bolts, the bolt holes will inevitably break the fibers, there will be obvious stress concentration at the edge of the hole, and the strength will be weakened; and the fatigue durability of adhesive bonding is not good. Once the adhesive interface is peeled off, the bearing capacity of the structure will drop sharply. Summary of the invention
[0003] The technical problem solved by the present invention is: to overcome the shortcomings of the prior art, and to propose a composite material and metal connection method based on femtosecond laser etching on the metal surface. In this method, when the femtosecond laser interacts with the metal material, the metal surface contains a large number of free electrons, and the free electrons in the femtosecond laser action area absorb photons and heat up on a femtosecond time scale. The free electrons transfer energy to phonons, and in this process the temperature of the electronic system gradually decreases, and the lattice temperature gradually increases. The laser is continuously irradiated, and when the lattice temperature is higher than the phase change critical value of the material, the material undergoes a phase change through melting or gasification, so that the metal is quickly melted and removed, and the required burr structure and set surface morphology are formed on the metal surface. Burrs in the shape of bevel teeth, honeycomb, vortex, hills, etc. are formed on the surface of the metal sheet by femtosecond laser roughening treatment, and then plasma treatment is used to increase the chemical energy and surface activity of the metal surface, increase the interlayer bonding strength between the metal sheet and the composite material, and achieve an effect similar to mechanical connection, with less damage to the composite material. The integrated molding of metal sheets and composite materials can greatly improve the interlayer bonding strength between the metal sheets and the composite materials. The prepared metal / fiber reinforced composite materials have the advantages of both metal sheets and composite materials, and have the characteristics of high specific strength, specific stiffness, low specific gravity, impact resistance, wear resistance and corrosion resistance.
[0004] The technical solution of the present invention is:
[0005] A method for connecting composite materials and metals based on femtosecond laser etching of metal surfaces, using plasma secondary treatment to improve the chemical energy and surface activity of the metal surface after roughening treatment. The composite material prepreg is directly laid on the roughened metal structure, and heated and pressurized to be cured and integrated. The "burrs" on the metal surface are embedded in the composite material, so that the "burrs" interact with the composite material, especially with the fibers, to form a mechanical interlock, which can enhance the interface strength between the metal and the composite material, and thus improve the bearing capacity of the connection between the metal and the composite material; the metal surface femtosecond laser etching and laminate composite preparation technology, characterized in that the surface of the metal plate in contact with the composite laminate is roughened by femtosecond laser etching technology, and then activated by plasma, and then the continuous fiber reinforced resin composite material prepreg is directly laid on the treated metal surface, and a high-strength combination of metal / composite laminate interface gradient composite is obtained by autoclave or compression molding process;
[0006] The specific steps of this method include:
[0007] Step 1, raw material preparation: polish the surface of the required metal sheet with 400, 800, 1200, 1500, and 2000 grit sandpaper to remove the oxide layer. Use industrial-grade ethyl acetate solvent or acetone to clean it, and cut the fiber prepreg into appropriate sizes according to the size of the required sheet.
[0008] Step 2: Femtosecond laser roughening: Place the cleaned and air-dried metal sheet into the workbench of the vacuum chamber of the femtosecond laser machine, and use a femtosecond laser for single-sided roughening.
[0009] Step 3: Plasma treatment: Clean the roughened metal sheet with industrial-grade ethyl acetate solvent or acetone and let it air dry naturally. Use low-temperature air plasma treatment equipment and a rotary plasma treatment nozzle for plasma treatment.
[0010] Step 4: Prepreg laying: Lay the roughened surface of the metal sheet facing the fiber prepreg, and lay the prepreg layer by layer according to the layup design;
[0011] Step 5: Curing and molding: Put the laid fiber prepreg and metal sheet into the autoclave for curing. The curing temperature is 80-140℃ and the curing time is 2h-3h.
[0012] Step 6: Demolding and trimming: Trim the cured sheet and remove the surface material edges.
[0013] The femtosecond laser texturing process in the further step 2 is:
[0014] (1) The required metal plates are polished with 400, 800, 1200, 1500, and 2000 grit sandpaper to remove the oxide layer, cleaned with industrial-grade ethyl acetate solvent or acetone, and placed in the vacuum chamber workbench of the femtosecond laser machine after air drying, and the femtosecond laser machine is started.
[0015] (2) The power of the femtosecond laser machine is 10-1000W, the laser pulse width is 200-800fs, the beam diameter is 0.3-0.7mm, the scanning speed is 0.1-5m / s, and the frequency is 0.1-1HZ. The laser center wavelength is 300-900nm, the focal length of the F-θ mirror is 250-300mm, the focus spot radius is 20-30μm, and the Rayleigh length is 2100-2400μm.
[0016] (3) Scanning according to different design paths, the roughening can form a height of 0.3-2.0mm and a density of 10-60 pieces / cm 3 The burrs are in the shape of oblique teeth, honeycomb, vortex and hill.
[0017] The plasma treatment process in the further step three is: the metal plate after laser roughening is cleaned with industrial-grade ethyl acetate solvent or acetone and then naturally dried, low-temperature air plasma treatment equipment is used, and a rotary plasma treatment nozzle is selected. The distance between the nozzle and the surface of the metal plate is 10 mm, the nozzle movement speed is 8 mm / s, the power is 800 W, the gas is air, the air pressure is 0.7 MPa, and the nozzle diameter is 40 mm.
[0018] In the further step one, the metal plate is a steel plate, an aluminum alloy plate or a titanium alloy plate.
[0019] Further, the fiber prepreg in step one is a mixture of one or more of carbon fiber prepreg, glass fiber prepreg, aramid fiber prepreg or basalt fiber prepreg.
[0020] In the further step 4, the fiber prepreg is a unidirectional fiber prepreg, a plain prepreg, a twill prepreg or a multi-axial prepreg.
[0021] Furthermore, the continuous fiber reinforced resin composite material is a mixed composition of one or more of carbon fiber continuous fiber reinforced resin composite material, glass fiber continuous fiber reinforced resin composite material, aramid fiber continuous fiber reinforced resin composite material or basalt fiber continuous fiber reinforced resin composite material.
[0022] The metal surface femtosecond laser etching and laminate composite preparation technology comprises the following steps: roughening the metal plate surface in contact with the composite laminate using femtosecond laser etching technology, then activating it with plasma, and then directly coating the treated metal surface with continuous fiber reinforced resin composite prepreg, and obtaining a high-strength combination of metal / composite laminate interface gradient composite through an autoclave or compression molding process.
[0023] Beneficial Effects
[0024] (1) Femtosecond laser peak power is greater than 10 12 W / cm2, pulse width in the femtosecond range (1fs = 10 -15 Compared with long pulse laser or continuous laser, the pulse width of femtosecond laser is much smaller than the electron-lattice relaxation time of the processed material (10 -10 ~10 -12 s), the electrons absorb the photon energy before the lattice heats up, so during the processing, the electrons and the lattice are in a non-equilibrium state, which inhibits heat diffusion, thereby greatly reducing the heat affected zone, reducing the thickness of the recast layer, and reducing surface microcracks. By adjusting the wavelength, pulse width, scanning mode and speed, surface periodic ripples, high aspect ratio micropores, microgrooves and other lattice structures can be achieved.
[0025] (2) Through femtosecond laser roughening of the metal interface, a multi-level microstructure is formed on the metal surface, and then plasma treatment is used to improve the chemical energy and surface activity of the metal surface, further increasing the interlayer bonding strength between the metal sheet and the composite material. This connection method can withstand higher loads than traditional bolt connections and adhesive joints of the same size, and absorbs more energy before breaking. It has significant advantages in the load-bearing and weight reduction of composite material structures and has potential application prospects.
[0026] (3) The prepreg is directly laid on the treated metal surface, and a high-strength composite body with a gradient interface of a metal / composite laminate is obtained through an autoclave or compression molding process. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a longitudinal cross-sectional view of the interlayer oblique tooth-shaped burrs of the titanium alloy plate / fiber reinforced composite material obtained in Example 1;
[0028] Figure 2 for Figure 1 A partial enlarged view of
[0029] Figure 3 This is a schematic diagram of the oblique tooth-shaped burrs on the surface of the titanium alloy plate in Example 1;
[0030] Figure 4 This is a picture of hill-like burrs on the surface of the 7075 aluminum alloy plate in Example 2;
[0031] Figure 5 This is a picture of honeycomb burrs on the surface of Q345 steel plate in Example 3;
[0032] Figure 6 This is a picture of swirl burrs on the surface of TC4 titanium alloy in Example 4. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0034] Example 1
[0035] A method for connecting a composite material and a metal based on femtosecond laser etching of a metal surface, the method comprising the following steps:
[0036] Step 1: Raw material preparation: Use 400, 800, 1200, 1500, and 2000 grit sandpaper to polish the surface of the required 3 mm thick TC4 titanium alloy sheet 1 to remove the oxide layer, and use industrial-grade ethyl acetate solvent or acetone to clean it. Cut the fiber prepreg 2 into appropriate sizes according to the size of the required sheet.
[0037] Step 2: Femtosecond laser texturing: Place the cleaned and air-dried TC4 titanium alloy sheet into the workbench of the vacuum chamber of the femtosecond laser machine and evacuate it. Use drawing software to edit the conventional array, with a dot row spacing of 1mm and a column spacing of 1mm. Select the first row of the conventional array as the conventional scanning unit and upload the conventional scanning unit to the control system of the femtosecond laser processing equipment. Start the femtosecond laser processing equipment, set the acceleration voltage to 150kV, heat the cathode filament, adjust the focusing current to the surface focusing state (about 2000mA), set the beam current to 2mA, the beam diameter to 0.4mm, the waveform to one beam, the frequency to 0.25HZ, the femtosecond laser scanning speed to 0.5m / s, the laser center wavelength to 515nm, the focal length of the F-θ mirror to 255mm, the focus spot radius to 25μm, and the Rayleigh length to 2106μm. Turn on the beam switch and observe the scanning situation. After the scan is completed, turn off the beam, turn off the scanning function, deflate the vacuum chamber, take out the test plate, and inspect the plate condition. The burr height on the plate surface is 1.2mm, and the density is 25 burrs / cm 3 The helical burrs, such as Figure 3 shown.
[0038] Step 3: Clean the roughened metal sheet with industrial-grade ethyl acetate solvent or acetone and let it air dry naturally. Use low-temperature air plasma treatment equipment and a rotary plasma treatment nozzle. The distance between the nozzle and the surface of the metal sheet is 10 mm, the nozzle movement speed is 8 mm / s, the power is 800 W, the gas is air, the air pressure is 0.7 MPa, and the nozzle diameter is 40 mm for plasma treatment.
[0039] Step 4: Prepreg laying: Lay the basalt fiber prepreg (400g / ㎡ fabric + 300g / ㎡ unidirectional fabric) according to the following steps: 400g plain fabric / 400g plain fabric / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -4 5° / 90° / 0° / 90° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 400g plain fabric / 400g plain fabric is laid with the textured surface of the metal sheet facing the fiber prepreg.
[0040] Step 5: Curing and molding: Put the laid fiber prepreg and metal sheet into vacuum bags and put them into the autoclave for curing. The temperature step is: 80℃ for 30 minutes → 90℃ for 10 minutes → 130℃ for 120 minutes, that is, keep at 80℃ for 30 minutes, then heat to 90℃ for 10 minutes, and then heat to 130℃ for 120 minutes. The pressure is 0.4MPa and the heating rate is 1.2℃ / minute.
[0041] Step 6: Demolding and trimming: Trim the cured sheet and remove the surface material edges.
[0042] The cross-sectional view of the connection surface between the titanium alloy plate and the fiber-reinforced composite material obtained is an interlayer oblique tooth-shaped burr, such as Figure 1 and Figure 2 shown.
[0043] Example 2
[0044] A method for connecting a composite material and a metal based on femtosecond laser etching of a metal surface, the method comprising the following steps:
[0045] Step 1: Raw material preparation: Use 400, 800, 1200, 1500, and 2000 grit sandpaper to polish the surface of the required 3 mm thick 7075 aluminum alloy sheet to remove the oxide layer, and use industrial-grade ethyl acetate solvent or acetone to clean it. Cut the fiber prepreg into appropriate sizes according to the size of the required sheet.
[0046] Step 2: Femtosecond laser texturing: Put the cleaned and air-dried 7075 aluminum alloy plate into the workbench of the vacuum chamber of the femtosecond laser machine and evacuate it. Use drawing software to edit the conventional array, the dot row spacing is 3mm, the column spacing is 3mm, select the first row of the conventional array as the conventional scanning unit, and upload the conventional scanning unit to the control system of the femtosecond laser processing equipment. Start the femtosecond laser processing equipment, set the acceleration voltage to 150kV, heat the cathode filament, adjust the focusing current to the surface focusing state (about 2000mA), set the beam current to 2.1mA, the beam diameter to 0.4mm, the waveform to 6 beams, the frequency to 0.5HZ, the femtosecond laser scanning speed to 1m / s, the laser center wavelength to 510nm, the focal length of the F-θ mirror to 250mm, the focus spot radius to 25μm, and the Rayleigh length to 2100μm. Turn on the beam switch and observe the scanning situation. After the scan is completed, turn off the beam, turn off the scanning function, deflate the vacuum chamber, take out the test plate, and inspect the plate condition. The burr height on the plate surface is 1.8mm, and the density is 20 burrs / cm 3 Hill-like burrs, such as Figure 4 shown.
[0047] Step 3: Plasma treatment process: same as step 3 in Example 1.
[0048] Step 4: Prepreg laying: Lay the carbon fiber prepreg (400g / ㎡ fabric + 300g / ㎡ unidirectional fabric) according to the following steps: 400g plain fabric / 400g plain fabric / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45 ° / 90° / 0° / 90° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 400g plain fabric / 400g plain fabric is laid with the roughened surface of the metal sheet facing the fiber prepreg.
[0049] Step 5: Curing and molding: Put the laid fiber prepreg and metal sheet into vacuum bags and put them into the autoclave for curing. The temperature step is: 80℃ for 30 minutes → 90℃ for 10 minutes → 130℃ for 120 minutes. Pressure: 0.4MPa, heating rate: 1.2℃ / minute,
[0050] Step 6: Demolding and trimming: Trim the cured sheet and remove the surface material edges.
[0051] Example 3
[0052] A method for connecting a composite material and a metal based on femtosecond laser etching of a metal surface, the method comprising the following steps:
[0053] Step 1: Raw material preparation: Use 400, 800, 1200, 1500, and 2000 grit sandpaper to polish the surface of the required 3 mm thick Q345 steel plate to remove the oxide layer, and use industrial-grade ethyl acetate solvent or acetone to clean it. Cut the fiber prepreg into appropriate sizes according to the size of the required plate.
[0054] Step 2: Femtosecond laser texturing: Place the cleaned and air-dried Q345 steel plate into the workbench of the vacuum chamber of the femtosecond laser machine for vacuuming. Use conventional drawing software to edit the scanning trajectory. The figure is a regular hexagon. The angle between two adjacent line segments is 120° and the length of each line segment is 1mm. And on the basis of the scanning trajectory, use conventional drawing software to edit the conventional array and staggered array, where the row spacing of the conventional array is 2mm and the column spacing is 2mm. Use image processing software to edit the corresponding scanning trajectory (honeycomb hexagon), set the grayscale value, where the grayscale value of the black font part is set to 20, and the grayscale value of other white areas is set to 0, save it as a bitmap file in BMP format, read the edited bitmap file into the control software, and upload the scanning unit to the control system of the femtosecond laser processing equipment. Start the femtosecond laser processing equipment, set the acceleration voltage to 150kV, heat the cathode filament, adjust the focusing current to the surface focusing state (about 2000mA), set the beam current to 2.6mA, the beam diameter to 0.4mm, the waveform to 3 beams, the frequency to 0.5HZ, and the femtosecond laser scanning speed to 0.5m / s. The laser center wavelength is 530nm, the focal length of the F-θ mirror is 250mm, the focus spot radius is 28μm, and the Rayleigh length is 2200μm. Turn on the beam switch and observe the scanning situation. After the scan is completed, turn off the beam, turn off the scanning function, deflate the vacuum chamber, take out the test plate, and inspect the plate condition. The height of the burr on the plate surface is 1.8mm, and the density is 25 / cm 3 Honeycomb-like protrusions, such as Figure 5 shown.
[0055] Step 3: Plasma treatment process: same as step 3 in Example 1.
[0056] Step 4: Prepreg laying: Lay the glass fiber prepreg (420g / ㎡ fabric + 300g / ㎡ unidirectional fabric) according to the following steps: 420g plain fabric / 420g plain fabric / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -4 5° / 90° / 0° / 90° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 420g plain fabric / 420g plain fabric is laid with the textured surface of the metal sheet facing the fiber prepreg.
[0057] Step 5: Curing and molding: Put the laid fiber prepreg and metal sheet into vacuum bags and put them into the autoclave for curing. The temperature step is: 80℃ for 30 minutes → 90℃ for 10 minutes → 130℃ for 120 minutes. The pressure is 0.4MPa and the heating rate is 1.2℃ / minute.
[0058] Step 6: Demolding and trimming: Trim the cured sheet and remove the surface material edges.
[0059] Example 4
[0060] A method for connecting a composite material and a metal based on femtosecond laser etching of a metal surface, the method comprising the following steps:
[0061] Step 1: Raw material preparation: Use 400, 800, 1200, 1500, and 2000 grit sandpaper to polish the surface of the required 3 mm thick TC4 titanium alloy sheet to remove the oxide layer, and use industrial-grade ethyl acetate solvent or acetone to clean it. Cut the fiber prepreg into appropriate sizes according to the size of the required sheet.
[0062] Step 2: Femtosecond laser texturing: Place the cleaned and air-dried TC4 titanium alloy sheet into the workbench of the vacuum chamber of the femtosecond laser texturing machine and evacuate it. Use drawing software to edit the conventional array, the dot row spacing is 4mm, the column spacing is 4mm, select the first row of the conventional array as the conventional scanning unit, and upload the conventional scanning unit to the control system of the femtosecond laser processing equipment. Start the femtosecond laser processing equipment, set the acceleration voltage to 150kV, heat the cathode filament, adjust the focusing current to the surface focusing state (about 2000mA), set the beam current to 2mA, the beam diameter to 0.4mm, the waveform to one beam, the frequency to 0.75HZ, and the femtosecond laser scanning speed to 0.5m / s. The laser center wavelength is 520nm, the focal length of the F-θ mirror is 270mm, the focus spot radius is 30μm, and the Rayleigh length is 2150μm. Turn on the beam switch and observe the scanning situation. After the scan is completed, turn off the beam, turn off the scanning function, deflate the vacuum chamber, take out the test plate, and inspect the plate condition. The burr height on the plate surface is 1mm, and the density is 20 / cm 3 The swirl-shaped burrs, such as Figure 6 shown.
[0063] Step 3: Plasma treatment process: same as step 3 in Example 1.
[0064] Step 4: Prepreg laying: Lay the aramid fiber prepreg (400g / ㎡ fabric + 280g / ㎡ unidirectional fabric) according to the following steps: 400g plain fabric / 400g plain fabric / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -45° / 90° / +45° / 0° / -4 5° / 90° / 0° / 90° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 90° / -45° / 0° / +45° / 400g plain fabric / 400g plain fabric is laid with the textured surface of the metal sheet facing the fiber prepreg.
[0065] Step 5: Curing and molding: Put the laid fiber prepreg and metal sheet into vacuum bags and put them into the autoclave for curing. The temperature step is: 80℃ for 30 minutes → 90℃ for 10 minutes → 130℃ for 120 minutes. Pressure: 0.4MPa, heating rate: 1.2℃ / min;
[0066] Step 6: Demolding and trimming: Trim the cured sheet and remove the surface material edges.
[0067] The products obtained in Examples 1-4 were subjected to pulling tests using a DeFelsko S / N AT14702 digital puller and TC4 plates and composite laminates without roughening treatment as reference samples. The comparison results are shown in Table 1:
[0068] Table 1 Pull-out strength of Examples 1-4
[0069]
[0070] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite material and metal connection method based on metal surface femtosecond laser etching, characterized in that The specific steps of this method include: Step 1: Surface treatment is performed on the metal sheets to be connected, and the fiber prepreg to be connected is cut into required sizes; Step 2, performing femtosecond laser single-sided roughening on the metal sheet after the surface treatment in step 1, and then cleaning it; Step 3, plasma treating the roughened surface of the metal plate in step 2; Step 4, laying the fiber prepreg cut in step 1 on the roughened surface of the metal plate that has been plasma treated in step 3 according to the laying design; Step 5: solidify the fiber prepreg and metal sheet laid in step 4, and trim the edges after solidification to complete the connection between the composite material and the metal sheet.
2. The method for connecting a composite material and a metal based on femtosecond laser etching of a metal surface according to claim 1, characterized in that: In the step 1, the method for surface treatment of the metal sheet is: Use 400, 800, 1200, 1500, and 2000 grit sandpaper to grind the surface of the metal sheet to remove the oxide layer, and then use industrial-grade ethyl acetate solvent or acetone to clean it.
3. The method for connecting a composite material and a metal based on femtosecond laser etching of a metal surface according to claim 1, characterized in that: In the step 1, the metal plate is a steel plate, an aluminum alloy plate or a titanium alloy plate; The fiber prepreg is at least one of carbon fiber prepreg, glass fiber prepreg, aramid fiber prepreg or basalt fiber prepreg, and the fiber prepreg is unidirectional fiber prepreg, plain prepreg, twill prepreg or multi-axial prepreg.
4. The method for connecting a composite material and a metal based on femtosecond laser etching of a metal surface according to claim 2, characterized in that: In the step 2, the method for performing femtosecond laser single-sided texturing is: Place the cleaned and air-dried metal sheet on the workbench of the vacuum chamber of the femtosecond laser machine, and use femtosecond laser for single-sided roughening. The power of the femtosecond laser machine is 10-1000W, the laser pulse width is 200-800fs, the beam diameter is 0.3-0.7mm, the scanning speed is 0.1-5m / s, the frequency is 0.1-1HZ, the laser center wavelength is 300-900nm, the focal length of the F-θ mirror is 250-300mm, the focusing spot radius is 20-30μm, and the Rayleigh length is 2100-2400μm.
5. The method for connecting a composite material and a metal based on femtosecond laser etching of a metal surface according to claim 2, characterized in that: In the step 3, the method of performing plasma treatment is: The roughened metal sheet is cleaned with industrial-grade ethyl acetate solvent or acetone and then naturally air-dried. Low-temperature air plasma treatment equipment is used, and a rotary spray plasma treatment nozzle is selected for plasma treatment. The distance between the nozzle and the surface of the metal sheet is 5-10mm, the nozzle movement speed is 5-10mm / s, the power is 700-1000W, the gas is air, the air pressure is 0.5-0.8MPa, and the nozzle diameter is 40mm.
6. The method for connecting a composite material and a metal based on femtosecond laser etching of a metal surface according to claim 2, characterized in that: In the step 5, the curing temperature is 80-140° C., and the curing time is 2 h-3 h.
Citation Information
Patent Citations
Composite material and metal connection structure and forming method thereof
CN103925267A
Plastic and metal integrated hot press forming device and method
CN106313526A
Method for connecting plastic and metal heterostructure
CN106393705A
Treatment method for promoting mechanical and metallurgical combination between thermal spraying coating film based interfaces
CN110468364A
Method for achieving laser heating and connecting on metal and continuous fiber reinforced composite material based on metal surface micro-cone structure design and machining
CN112497760A
Cited By
Titanium alloy artificial cochlea laser cutting integrated forming machining method
CN119973569A
Method for inducing resin secondary permeation based on laser CFRP interface pretreatment
CN120885876A
Metal-polymer composite structure and processing technology
CN120941739A